Figurativeness Matters in the Second Language Processing of Collocations: Evidence From a Self‐Paced Reading Experiment. Issue 1 (1st September 2022) - Shi, Jinfang; Peng, Gang; Li, Dechao
Abstract: This study reports on a self‐paced reading experiment exploring whether the figurativeness of collocations affects L2 processing of collocations. The participants were 40 English native speakers and 44 Chinese‐speaking English foreign language learners (including doctoral, postgraduate, and undergraduate students). To ensure that the effect emerged from the figurativeness of collocations rather than other item‐related confounds, this study added a literal–literal comparison (e.g., choose a career vs. choose a house ) as a control to the experimental figurative–literal comparison (e.g., build a career vs. build a house ). Results showed that L2 speakers processed figurative collocations more slowly than literal collocation controls but native speakers did not. Importantly, this processing cost for figurative collocations in L2 speakers varied by L2 proficiency but not phrase familiarity. We discuss the results in terms of the dual‐route model of formulaic and novel language processing and also incorporate them into the literal salience model of bilingual figurative processing. Abstract :